EFEKTIVITAS PELAKSANAAN PROGRAM SUMBANGAN PEMBINAAN PENDIDIKAN (SPP) GRATIS BAGI MAHASISWA KABUPATEN PANGKEP (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The purpose of this research was conducted to determine the effectiveness of the implementation of the free educational contribution program (SPP) for students in Pangkep district. The research method used is descriptive qualitative research. The number of informants in this study were 4 people. Data collection techniques using interviews, observation, and documentation. The results of the study show that the effectiveness of implementing the free SPP is seen from aspects 1) The accuracy of program targets, namely the extent to which program participants are right on target, 2) Program socialization is carried out by the education office by utilizing social media, correspondence, and direct outreach to prospective recipients free SPP scholarships 3) the aim of the program is to improve the quality of human resources who are disciplined and increase efficiency and effectiveness to meet the quality and productivity of superior human resources 4) program monitoring is carried out to identify and anticipate problems that arise so that action can be taken as early as possible